Antibiotic and Anticoagulation Therapy in Lemierre's Syndrome: Case Report and Review. (2nd January 2019) - Campo, Flaminia; Fusconi, Massimo; Ciotti, Mario; Diso, Daniele; Greco, Antonio; Cattaneo, Carlo Guglielmo; de Vincentiis, Marco
Abstract : Lemierre's syndrome is a rare and fatal disease and is also known as the forgotten disease to describe the rarity of this syndrome in the antibiotic era. However, in the last 20 years, the incidence of this disease has been increasing. Authors report a case of Lemierre's syndrome with extensive venous thrombosis involving right internal jugular veins with extension to the sigmoid and lateral sinus and also review the literature on the use of anticoagulant therapy in Lemierre's syndrome. A computerized Medline study was carried out through the use of PUBMED: using the Medical Subject Headings terms 'Lemierre Syndrome/diagnosis' and words 'Lemierre's syndrome and anticoagulation'. From this, authors found 64 articles from 2002 to January 2018 with a total of 165 patients. The purpose of our review is to emphasize that antibiotic therapy should be started immediately, while anticoagulant therapy should be started in selected cases. Anticoagulation should be carried out in absence of any contraindication or presumed risk following clinical anticoagulation guidelines and only in patients with poor clinical response despite antibiotics therapy, predisposing thrombophilia and intracranial thrombosis.